Impact of the central bank's communication on macro financial outcomes - Tetiana Yukhymenko; Oleh Sorochan (Graduate Institute of International and Development Studies, 2024)
The study explores the impact of central bank communications on a range of macro-financial indicators. Specifically, we examine whether information posted on the National Bank of Ukraine (NBU) website influences foreign exchange (FX) markets and the inflation expectations of experts. Our main results suggest that the NBU's statements and press releases on monetary policy issues matter. For instance, we find that exchange rate movements and volatility are negatively correlated with the volumes of publications of the NBU on its official website. However, this effect is noticeably bigger for volatility than for exchange rate changes. The impact of communication on FX developments is the strongest a week after the news release, and it persists further. Furthermore, inflation expectations of financial experts, though indifferent to all NBU updates, turn out to be sensitive to monetary policy announcements. The letter reduces the level of expectations and interest rates.
Keywords: E58; E71; C55; 330; central bank communications; monetary policy; FX market; text analysis